Hubungan Kebutuhan Tidur Dengan Aktivitas Fisik Pada Lansia - Wahyuni, Endah Trie; susilowati, Tri; Imamah, Ida Nur (Jurnal Keperawatan Muhammadiyah, 2020)
Background: Â Disability prevalence in the elderly in Indonesia as much as 1.6% experienced total dependence, 1% experienced heavy dependence, 74.3% were able to carry out independent activities, 22% could only do light activities, and 11% were able to carry out moderate activities. Results obtained in Central Java province 1.8% experienced total dependence, 1% experienced severe dependence.Objective: Analyze the relationship between the need for sleep and physical activity in the elderly at the Bhakti Surakarta Dharma Nursing Home. Method: This type of research is quantitative, with an observational analytic method with a cross sectional design, sampling using the purpose sample method with a sample of 44 respondents with a research instrument using a GPAQ (Global physical activity questionnaire) from physical activity. This data analysis uses Fisher Test. Results: Statistical test results on respondents showed Ïvalue (0.018) <0.05, so that there was a significant relationship between the need for sleep and physical activity. Conclusion: There is a relationship between the need for sleep and physical activity in the elderly at the Surakarta Darma Bhakti Nursing Home.